An Experimental Test of the Global-Game Selection in Coordination Games with Asymmetric Players - Frank Heinemann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
In symmetric binary-choice coordination games, the global-game selection (GGS) has been proven to predict a high proportion of observed choices correctly. In these games, the GGS is identical to the best response to Laplacian beliefs about the fraction of players choosing either action. This paper presents an experiment on asymmetric games in which the GGS differs from the best response to Laplacian beliefs. It shows that the best response to Laplacian beliefs is a better predictor of behavior in these games than the GGS. In the considered games, the GGS provides poor guidance and also fails to give the right qualitative comparative statics predictions. Simple cognitive hierarchy models yield better predictions. The best response to a Laplacian belief about the distribution of other players' actions yields the best prediction. Comparing maximum likelihood estimates for four probabilistic models shows that an estimated global-game equilibrium fits worse than a rather simple level-k or Laplacian-belief model combined with a standard error-response function.
Keywords: C72; C91; D81; 330; coordination games; equilibrium selection; global game; Laplacian beliefs; private information; network effects